Eco-Friendly Accounting: Rise Of Green Accounting In Indonesia - Wardi, Jeni; Nasution , Nurliana; Lubis, Nurhayani (Universitas Lancang Kuning, 2025)
This study aims to determine the implementation of Green Accounting in Indonesia and to understand its relationship with company performance. The research employs a literature review method, which involves collecting, analyzing, and synthesizing information from various sources to develop a comprehensive understanding of the topic. The objects of this study are three journal articles: Green Accounting Era 4.0 Towards Society 5.0, Analysis of Green Accounting Implementation on the Financial Performance of PT Unilever Indonesia, and Green Accounting: A Review Paper. The findings reveal that Green Accounting plays an important role in improving company performance by integrating environmental and social aspects into financial reporting. The adoption of Green Accounting encourages companies to operate sustainably and be more accountable to stakeholders. Furthermore, the study highlights changes in the accountant’s role in the era of the Industrial Revolution 4.0 and Society 5.0, where technology drives transformation in accounting practices. Accountants are required to enhance their competencies, particularly in adapting to technological advancements that support environmental sustainability and corporate performance. In conclusion, Green Accounting not only contributes to environmental protection but also improves transparency, efficiency, and the long-term value of companies in the digital era.